Pandangan Masyarakat Terhadap Mural di Ruang Publik Kota Padang - Viona Dwi Dahlia; Yahya Yahya (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
Mural means painting on a large, permanent wall/wall media. The purpose of this research is to determine the existence of mural forms, determine the role of murals, and determine the public's views on murals in Padang City. This type of research is qualitative research. The research was conducted in Padang City with a focus area in Gang Muhajirin, Dadok nggul Hitam, Jl Bakti Parupuk Tabing and around Taplau, Padang City. Data collection uses observation, interviews, documentation. Data analysis uses Milles Huberman analysis. The research results show that the public is very enthusiastic and appreciates murals as a form of art that beautifies the city. The existence of murals is able to establish close relationships between the art community and the surrounding community. The role of murals in Padang City society can be used as a media for education, increasing social awareness, criticism, communication media and adding to the aesthetic value of an area. People's views on murals can be very varied and complex depending on their understanding of murals.